Creative Marketing Strategies and Campus Promotions in Attracting Community Interest in Higher Education - Elpisah; Putera, Wahyudi; Suarlin, S.; Sulolipu, Andi Annisa; Haslindah (Advances in Social Sciences Research Journal, 2023)
STKIP Pembangunan which is now changing its name to Patompo University of Makassar City is currently the choice of higher education studies. The purpose of this study was to analyze the creative marketing strategies carried out by the Patompo University Public Relations team in attracting new prospective students and to find out whether the promotional strategies carried out by the Patompo University Public Relations team have been carried out optimally. The research method used is descriptive qualitative research method. The data collection technique used was in-depth interviews with the Manager of Patompo University’s Public Relations team. In addition, discussions were held with 3 respondents as informants to find out the creative marketing activities that have been carried out by the Patompo University Public Relations team to attract new prospective students. The result of this research is that the creative marketing strategy carried out by the Patompo University team has been running well, successfully achieving the target, while the promotion strategy through the image of Patompo University campus is very good, because the majority of informants prefer Patompo University to take education-oriented majors than other private campuses in Makassar City. The conclusion of this research is that using creative marketing strategies in promoting Patompo University is very effective, but the Patompo University team must also consider establishing good cooperation with various online media outside the campus as well as the Government sector in this case the local, provincial and central government in order to get the best results: